Atlantyda jako mit nie-grecki, czyli o mitach w kulturze popularnej - Czarcińska, Katarzyna (Collectanea Philologica, 2015)
The article focuses on the issue of reception of ancient myths in popular culture. As popularculture is known for vast use of different ancient myths in many productions, the question may beraised, if they can be still named as ‘ancient’. With the example of the drowned peninsula of Orrin Guild Wars video games, which is compared with the Atlantis isle of Plato, the article provesthat despite structural similarity of the story, these two are different myths. The myth of Atlantisis shaped by the Greek culture, which is oriented on the past, with strong conviction that the humanrace is heading towards destruction. The story of Orr reflects immersion in present time and the needto bury the past once and forever. Therefore, popular culture creates its own mythology, which is namedas the mythology of popular culture.